2015
DOI: 10.1371/journal.pone.0130212
|View full text |Cite
|
Sign up to set email alerts
|

Contraception and Unintended Pregnancy among Unmarried Female University Students: A Cross-sectional Study from China

Abstract: This study aims to understand the level of contraceptive knowledge and attitudes towards contraception, and then to explore the association between the contraceptive behavior and unintended pregnancy in unmarried female university students in China. A cross-sectional study was conducted of university students in 49 universities across 7 cities in China from September 2007 to January 2008. We distributed 74,800 questionnaires, of which 69,842 were returned. In this paper, the data from 35,383 unmarried female u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
47
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 23 publications
7
47
1
3
Order By: Relevance
“…This probability of behavioural change wheel is supported by reports of other studies indicating that socioeconomic background to students influences their access to and use of contraceptives [56][57][58] . Perhaps, what seems to be missing in the discourse is that pregnancy rates among the girls in university community is apparently very low, which is indicated by a highly maintained uninterrupted education.…”
Section: Knowledge and Usage Of Contraceptive Among University Studentssupporting
confidence: 76%
“…This probability of behavioural change wheel is supported by reports of other studies indicating that socioeconomic background to students influences their access to and use of contraceptives [56][57][58] . Perhaps, what seems to be missing in the discourse is that pregnancy rates among the girls in university community is apparently very low, which is indicated by a highly maintained uninterrupted education.…”
Section: Knowledge and Usage Of Contraceptive Among University Studentssupporting
confidence: 76%
“…Studies among undergraduates have revealed similar outcomes to our study 12,28 . Since no contraceptive method has 100% effectiveness, it is advocated that emergency contraceptive pill be routinely added to the primary contraceptive, offering a second chance to prevent unwanted pregnancy 30 .…”
supporting
confidence: 87%
“…Studies among undergraduates in Tanzania reported that condoms were favored most, followed by withdrawal and periodic abstinence 12,28 .…”
mentioning
confidence: 99%
“…Only local undergraduate students were selected in this study. The questionnaire had been obtained from published article [6]. …”
Section: Methodsmentioning
confidence: 99%